Effect of liquidity on company’s stock market performance - Dereniuk, Valeriia (2020)
The asset liquidity plays an important role in investors’ decisions. The idea of the study is to investigate the impact of liquidity on companies’ stock return based on the stock and financial data of European companies from 2015 until 2018. Amihud’s illiquidity measure is used as a proxy for illiquidity and calculated as a weighted average of stock returns based on the traded volume. As controlling variables we used beta as a measure of systematic risk, stock risk, size of the company and book-to-market ratio. The statistical analysis was done on 152 companies that were selected for the final sample using the statistical software - Eview 11. We found that liquidity has a negative relationship with companies’ stock return. This results support the hypothesis of aversion towards illiquidity.